Cloud Computing-Based M-Government - Karim, Faten (Informatica, 2022)
In recent time, several governments throughout the world have implemented cloud services, promising citizens a number of proven benefits such as cost savings, data management, rapid scaling, and increased public service delivery, resource sharing, and extended communication channels. Despite the importance of this field, the majority of previous studies focused on the development of cloud computing and the possibility of its application to implement e-government services. These studies were not concerned with the extent of governments' orientation towards implementing e-government and exploiting it in the service of citizens. Therefore, in this paper, an overview is presented on the level of M-Government implementation based on cloud computing and benefit from its services in many developed and developing countries of the world, especially the Kingdom of Saudi Arabia.